Guide for monitoring child development in Indian setting - Mustafa DCH, (DNB)2, Balaji PA MD, PGDMLE1, S M Dhaded MDDM3, S S Goudar MD, MHPE4, Syed Sadat Ali MD, DHHM1*, Syed Ahmed (International Multidisciplinary Research Journal, 2011)
A study to know the prevalence of neurobehavioral developmental delay among children aged three years residing in rural communities of India using Guide for monitoring child development (GMCD). About 530 children at three years were assessed for developmental delay. The GMCD was administered to mothers by a trained interviewer. Prevalence of neurobehavioral developmental delay was estimated and validity of GMCD screening tool was monitored in Indian children. Chi-square test was used to compare categorical variables. Differences were considered significant at P<0.05 level. The results showed that the prevalence of developmental delay assessed by GMCD was 48.5%. Children displayed delay in activity for self (46.8%), communication (39.2%) and understanding skills (13.2%). The results suggest a high prevalence of neurobehavioral developmental delay and poor child health in this rural population. Implementing early intervention programs may ameliorate the long term consequences of these developmental disorders. In the present study GMCD showed as a better validity screening tool for assessment of neurobehavioral developmental delay in children.